Некоторые направления синтеза новых решений в области совершенствования процессов жидкостной экстракции для пищевой промышленности - Shegelman I. R., Vasilyev A. S., Shchukin P. O. (Science, education, society: trends and prospects, 2017)
it is shown that the improvement of the processes of liquid extraction for the food industry is aimed at justifying their rational regimes, accelerating processes, and automating them.
Keywords: пищевая промышленность; патент; patent; food industry; жидкостная экстракция; liquid extraction